Editorial note: Welcome to the year 2021 and Volume 24 - Davids, Razeen; Assounga, Alain G (African Journal of Nephrology, 2021)
On behalf of the editors and the editorial board of African Journal of Nephrology (AJN), I wish all our readers, authors and reviewers a very happy New Year. This year could not have come soon enough after we all experienced a turbulent 2020 which was marked by the global COVID-19 pandemic, the worst in recent memory. I request that we all take a minute to reflect on and honour those colleagues and family members who passed away in 2020. In particular, I wish to mention Dr Anthony Were, who was the current AFRAN president, Prof Mohamed Abdullah, the second AFRAN President, and Prof Jacob Plange-Rule, from Ghana. We will forever be grateful for their contributions to nephrology in Africa. Of the 2020 publications, I wish to highlight the guidelines for treatment of COVID-19 in Africa. This important document was the product of a fruitful continent-wide collaboration and outlines an approach to the management of COVID-19 in patients with kidney disease in Africa. We are very pleased to announce that the South African Department of Higher Education and Training has now included Directory of Open Access Journals (DOAJ)-listed journals among those which qualify for research subsidies for South African authors. AJN achieved inclusion into DOAJ in 2019. Running the Journal is a collective effort. I wish to acknowledge all who contributed in years past, including our founding editor, the late Prof Maher Ramzy, and I wish to thank our current editorial team, Deputy Editor Prof Razeen Davids, Associate Editors Prof Faiçal Jarraya, Dr Fergus Caskey and Prof Sarala Naicker, and all our authors, reviewers and readers. Finally, as we start the New Year in the middle of the second wave of the COVID-19 pandemic, I wish a successful and safe New Year to all. Alain G Assounga Editor-in-Chief